If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=-6+3u
We move all terms to the left:
-12-(-6+3u)=0
We add all the numbers together, and all the variables
-(3u-6)-12=0
We get rid of parentheses
-3u+6-12=0
We add all the numbers together, and all the variables
-3u-6=0
We move all terms containing u to the left, all other terms to the right
-3u=6
u=6/-3
u=-2
| 5(x+1)+35=-3x | | 6=3/7w | | 6=3/4w | | (4x+6)+(2x-10)=44 | | 7-y/2=21 | | 20x-4=3(4x+2) | | 4x^2/5-x/5-3/10=0 | | 22–3y=1 | | 6x+4x-15=30-5x | | 11/x=8/3 | | x^+2x+1=0 | | 3x-6=30-x | | 2=3n+1/2 | | 30+(3c+4)=2(c+7)+c | | N=g(-2)+3 | | 12x=14=12x+5 | | -16w+14+4w=-14w-16 | | 7x÷3=2x-12 | | 3=5z+18 | | 11+3a=-15-4a | | t÷3-8=9 | | 45-5t=25 | | 7(x+5=-7(x+5) | | -2a+14=44* | | 4x+5x-42=70 | | 6x+7x-68=34-4x | | 4(x-4)=8(2x-14) | | -3-5d=14+12d | | 14x+8=48 | | 3/4=n/5 | | √2x+6=√X+10 | | 20-11x=10+7x |